State Marriage and Civil Marriage: The Role of State Policy on Interreligious Marriage in Central Java - Anthin Lathifah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2020)
This article discusses interreligious marriage in Central Java, especially in Surakarta, Semarang City and Jepara; places where the policies of stakeholders on judicial system, the role of demographic officials and religious leaders heavily influence each other. The policies of the State Court as an institution authorized to determine interreligious marriage vary from one to another area. For example, the Surakarta State Court receives the petition and establishes interreligious marriage, in contrast to the State Court in Semarang and Jepara which deny the petition of interreligious marriage. It is influenced by several things, namely the understanding of the regulation of marriage laws in Indonesia as well as religious understanding and role of its religious leaders. In the context of state and civil society relations, interreligious couples whose petitions are rejected consider it unfair; even those whose petition is accepted also deem it unfair since they regard their marriage as a civil marriage only, not desired by the state.Artikel ini membahas tentang perkawinan beda agama di Jawa Twngah, khususnya di Surakarta, Kota Semarang dan Kabupaten Jepara, tempat-tempat dimana kebijakan para pemangku kepentingan tentang sistem peradilan, peran pejabat demografik dan pemimpin agama saling mempengaruhi satu sama lain. Kebijakan Pengadilan Negeri sebagai lembaga yang berwenang menentukan perkawinan beda agama bervariasi dari satu daerah dengan daerah yang lain. Pengadilan Negeri Surakarta menerima petisi dan menetapkan perkawinan beda agama, berbeda dengan Pengadilan Negeri Kota Semarang dan Kabupaten Jepara yang menolak permohonan perkawinan beda agama. Perbedaan kebijakan tersebut dipengaruhi oleh beberapa hal, yaitu pemahaman tentang peraturan perundang-undangan perkawinan di Indonesia, pemahaman agama dan peran para pemimpin agama. Dalam konteks hubungan negara dan masyarakat sipil, pasangan antara agama yang permohonannya ditolak menganggapnya tidak adil; bahkan mereka yang permohonannya diterima juga menganggap itu tidak adil karena mereka menganggap merkawinannya hanyalah perkawinan sipil, yang tidak diinginkan oleh negara.